Rancang Bangun Prototipe Heat Exchanger Type Shell and Tube Arah Aliran Searah - Azmain N Hatuwe; Anisa Muhammad Hayoto; Kristofol Waas (Journal Mechanical Engineering, 2025)
This research aims to analyze the design and fabrication of a parallel-flow shell-and-tube heat exchanger prototype. The research was motivated by the need for concrete and effective practical learning media in the Mechanical Engineering Department of Ambon State Polytechnic, which is currently limited to theoretical material. The design method for this device uses a "build and build" approach. This design combines a 6 mm diameter aluminum pipe for the hot fluid tube and a 4 inch diameter galvanized iron pipe as the shell for the cold fluid. The fluid used for the hot and cold sides is water. The mass flow rates applied to the hot and cold fluids are 0.089 kg/s and 0.12572989 kg/s, respectively. The design calculations resulted in the creation of a prototype exchanger with a shell length of 0.5 m, an outer tube diameter of 0.006 m, and 74 aluminum tubes. Leakage testing was conducted using compressed air at 16 psi for 5 minutes. No leaks were found during the test. Keywords : heat exchanger,, shell and tube, parallel flow